The Perception of EFL Libyan University Students Towards the Potential Advantages of Phonetic Symbols - Nisreen , Al-Shredi (International Journal of Linguistics and Translation Studies, 2023)
The objective of this study is to investigate the perception of Libyan university students towards the potential advantages of phonetic symbols in learning English language. The study encompasses 30 students from the fifth, sixth, seventh and eight semesters studying all in the English Department in the Faculty of Languages at the University of Tripoli. The data is collected through a close-ended questionnaire distributed online via google forms. The results suggest that the students’ perception towards the potential advantages of phonetic symbols are seemingly positive. The findings arrive at a conclusion that students’ views towards the advantages of familiarity, visual- support, usefulness and awareness-raising of phonetic symbols are relatively positive. However, certain responses show that student have almost negative views towards the perceived ease of phonetic symbols as well as the potential of autonomous learning. The study finally suggest that the students still find phonetic symbols difficult to understand and use due to their insufficient knowledge or lack of total awareness.